Therapeutic uterine artery embolization in a life-threatening postpartum hemorrhage: a case report - Leila Pourali; Sedigh Ayati; Masoud Pezeshkirad; Mansooreh Sadat Golmohammadi (Reviews in Clinical Medicine, 2017)
Postpartum hemorrhage (PPH) is one of the most common complications of delivery and is a major cause of maternal morbidity and mortality. The aim of this report is to introduce a case of therapeutic uterine artery embolization (UAE) in a life-threatening postpartum hemorrhage. A 26-year old G3P3 woman with severe postpartum hemorrhage after 50 days of delivery referred to the emergency unit of an academic hospital of Mashhad University of Medical Sciences, Iran with third episode of vaginal bleeding. Gynecological examination and sonography were completely normal. Hypovolemic shock that was managed by fluid and blood replacement-therapy with uterotonic medical agents including oxytocin infusion (40 unit/lit), injection of 0.2 mg methyl-ergonovin and 1000 µg rectal misoprostol. Uterine artery embolization was planned due to unremitting severe hemorrhage. Embolization resulted in successful control of hemorrhage and the patient was discharged. At 6 months follow-up, no adverse events pertinent to embolization were noted. Therefore, UAE is suggested as a useful method for controlling intractable bleeding due to postpartum hemorrhage.